Framing Gender in Romanian 2019’s Presidential Elections. A Comparison between Broadsheet and Tabloid Content Newspapers - Campian, Veronica; Iancu, Ioana (Information & Media, 2023)
As women are more and more represented in all domains, a political arena with a feminine presence becomes of great interest. By building off prior work on the same topic (Dan & Iorgoveanu, 2013), the present paper aims to analyze the way Viorica Dăncilă and Klaus Iohannis, as political candidates, are portrayed within 2019 Presidential elections’ campaign. The inquiry is conducted by quantitatively and qualitatively comparing quality and tabloid content. The premise of the study is twofold. First, the article investigates if there is a gender bias in the news coverage of the two main candidates for the Presidential. Second, the aim is to identify if there are differences between quality and tabloid content. The data show that the woman candidate is mostly visible in tabloid media, that men’s topics are predominant, and that the man candidate is presented as being more viable for the office.